Experimental Study of Contour Sources of Noise from Airland without Crew with DLE Gas Engine-30 and the Most Noise Counter Optimized by Using Method of Active Noise Control with a Variety of 45°, 90°,135° - Alfisyahrin - -; Ikhwansyah Isranuri; Muhammad Rafiq Yanhar; Syukriyadin -; Deni Sigar (Universitas Islam Sumatera Utara, 2026)
Unmanned Aerial Vehicle is a flying machine aircraft that can be controlled remotely to perform its function. As with other machines, noise problems are unavoidable. One of the components contributing to noise in aircraft is the engine. To reduce the noise level produced, it is necessary to study and research further the noise factor through acoustic science by conducting experimental and simulation tests using ANSYS software which was developed in Noise Control science. In this case, simulation has the advantage because it can be used to analyze more complex systems and conditions that can be adjusted and also have more accurate results. This study aims to make comparisons and determine the optimal sound reduction angle in the experimental method and noise simulation on the DLE GAS ENGINE-30 drone engine. Based on the results of experimental tests conducted on the DLE Gas Engine-30 engine, the optimal reduction value is obtained with an engine speed of 2000 RPM on the z- axis, a distance of 0.75 m and an angle of 45° with a reduction value of 4.1 dB and at 3000 RPM engine speed is on the x- axis, a distance of 1.25 m and an angle of 135° with a reduction value of 3.5 dB. While testing based on the results of simulation testing conducted on the DLE Gas Engine-30 engine, the optimal reduction value is obtained with an engine speed of 2000 RPM on the z+ axis, 1 m distance and 45° angle with a reduction value of 9.1 dB and at 3000 RPM engine speed found on the z+ axis, a distance of 0.75m and an angle of 135° with a reduction value of 12.8 dB.